2010
DOI: 10.1089/cell.2009.0068
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Histone Acetylation of Cloned Embryos, But Not Donor Cells, by Sodium Butyrate Improves TheirIn VitroDevelopment in Pigs

Abstract: Previous studies have demonstrated that increased histone acetylation in donor cells or cloned embryos, by applying a histone deacetylase inhibitor (HDACi) such as trichostatin A (TSA), significantly enhances their developmental competence. However, its effect may vary with the type of HDACi and the target species, with some research showing nonsignificant or detrimental effects of TSA on in vitro and in vivo development of embryos. In this study, we show that sodium salt of butyric acid, a short-chain fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 45 publications
2
59
1
4
Order By: Relevance
“…32 In pigs, sodium butyrate supplementation improved embryo development in vitro and enhanced gene expression involved in early development. 33,34 Lastly, a recent study in rats suggested that hypertension was associated with reductions in the proportions of butyrate-producing bacteria but increases in bacteria that produce lactate. 35 Here, Odoribacter abundance is inversely correlated with both blood pressure and PAI-1.…”
Section: Hypertensionmentioning
confidence: 99%
“…32 In pigs, sodium butyrate supplementation improved embryo development in vitro and enhanced gene expression involved in early development. 33,34 Lastly, a recent study in rats suggested that hypertension was associated with reductions in the proportions of butyrate-producing bacteria but increases in bacteria that produce lactate. 35 Here, Odoribacter abundance is inversely correlated with both blood pressure and PAI-1.…”
Section: Hypertensionmentioning
confidence: 99%
“…Of these strategies, one widely used is to treat reconstructed SCNT embryos, but not the donor cells, with histone deacetylase inhibitors (HDACi), such as trichostatin A (TSA), 6-(1,3-dioxo-1H, 3H-benzo [de] isoquinolin-2-yl)-hexanoic acid hydroxyamide (Scriptaid), sodium butyrate and valproic acid. It has been demonstrated that histone deacetylase inhibitor treatment after SCNT can improve both in vitro development of SCNT embryos to the blastocyst stage and in vivo development to term following embryo transfer Cervera et al, 2009;Zhao et al, 2009aZhao et al, , 2010Das et al, 2010;Himaki et al, 2010a;Miyoshi et al, 2010). However, these treatments may be with some level of toxicity, as one group has reported that offspring from TSA-treated rabbit embryos did not survive to adulthood (Meng et al, 2009).…”
Section: Methods To Improve Nuclear Remodeling and Reprogrammingmentioning
confidence: 99%
“…However, these treatments may be with some level of toxicity, as one group has reported that offspring from TSA-treated rabbit embryos did not survive to adulthood (Meng et al, 2009). The exact mechanism by which the HDACi treatment significantly improves the cloning efficiency remains largely unknown, although it has been shown to increase levels of global histone acetylation after HDACi treatment which may subsequently change the structure of chromatin and improve nuclear reprogramming (Shi et al, 2008;Iager et al, 2008;Das et al, 2010). Accruing investigations have demonstrated that abnormal DNA methylation patterns contribute to the lower developmental competency of SCNT derived embryos (Kang et al, 2001(Kang et al, , 2002Bourc'his et al, 2001;Santos et al, 2003;Wrenzycki et al, 2006), suggesting the inability of oocyte to fully restore the DNA methylation pattern of differentiated donor nuclei to that of normal totipotent 1-cell stage embryos.…”
Section: Methods To Improve Nuclear Remodeling and Reprogrammingmentioning
confidence: 99%
“…In fact, different types of epigenetic modifications can interact with each other (as shown in Figure 2); the abnormality in one type of epigenetic modification must result in the abnormality in other types of epigenetic modifications. For example, due to incomplete DNA demethylation, cloned embryos would exhibit lower level of histone acetylation and H3K4 methylation, and higher level of H3K9 methylation, that is why treatment of cloned embryos with histone deacetylase inhibitor (trichostatin A, sodium butyrate, Scriptaid, and VPA), as well as inducing express of H3K9me3 demethylases JMJD2B, could improve their developmental ability (Rybouchkin et al 2006;Van Thuan et al 2009;Das et al 2010;Xu et al 2012;Antony et al 2013). …”
Section: Main Barricades Of Reprogramming Somatic Cells By Oocytesmentioning
confidence: 99%